Pengaruh Ukuran Perusahaan, Komite Audit, dan Kepemilikan Publik Terhadap Audit Delay (Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar di Bursa Efek Indonesia Periode 2016 – 2018) - Endang Dwi Wahyuningsih; Akayati Akayati (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This study aims to examine the effect of Firm Size, Audit Committee, and Public Ownership on Audit Delay in manufacturing companies in the Basic and Chemical Industries sector listed on the Indonesia Stock Exchange during the period 2016-2018. Audit Delay is an important indicator that reflects the duration of time required to complete an audit of financial statements. This study uses a quantitative approach with secondary data taken from the annual reports of companies listed on the Indonesia Stock Exchange. The population of this study consists of manufacturing companies in the Basic and Chemical Industries sector listed on the Indonesia Stock Exchange during the period 2016-2018. The sampling technique used is purposive sampling, resulting in a sample of 168 companies. The independent variables in this study are Firm Size, Audit Committee, and Public Ownership, while the dependent variable is Audit Delay. Data analysis was conducted using multiple linear regression. The results show that: first, Firm Size has a significant negative effect on Audit Delay, meaning that the larger the company size, the faster the audit process. Second, Public Ownership has a significant positive effect on Audit Delay, indicating that companies with public ownership tend to take longer to complete audits. Third, the Audit Committee does not have a significant effect on Audit Delay, meaning that the presence of an audit committee does not influence the audit completion time. This study contributes to a better understanding of the factors affecting audit delay in public companies.